Knowledge, attitudes, and perceptions of influenza vaccine among pregnant women in Minhang District, Shanghai - Yan Lu; Xiaoya Fu; Ling Xu; Jia Lu (Taylor & Francis Group, 2024)
This study aimed to assess the attitudes and willingness of pregnant women to receive the influenza vaccine and the factors influencing their decisions. A sample survey was conducted among pregnant women receiving prenatal care at various medical institutions in Minhang District, Shanghai, from March to June 2023. The survey included inquiries about demographic information, knowledge, and perception of influenza disease and influenza vaccine. Logistic regression models and chi-square tests were used to analyze the data. 6.9% (78/1125) of participants considered receiving the influenza vaccine during pregnancy. Participants with graduate education or above (OR = 4.632, 95%CI: 1.046-20.517), non-office workers (OR = 2.784, 95%CI: 1.560-4.970), and participants whose spouses were not office workers (OR = 0.518, 95% CI: 0.294-0.913) were significantly associated with high intent to vaccinate. Participants with superior knowledge (>30 points) exhibited greater willingness (p < .001). Participants who viewed post-influenza symptoms as mild had a significantly lower willingness to vaccinate during pregnancy (2.3%), compared to those who disagreed (p = .015). Conversely, those recognizing a heightened risk of hospitalization due to respiratory diseases in pregnant women post-influenza were significantly more inclined to vaccinate during pregnancy (8.8%) (p = .007). Participants recognizing benefits uniformly expressed willingness to receive the influenza vaccine during pregnancy (p < .001), while those perceiving barriers uniformly rejected vaccination (p < .001). Higher education, non-office worker status, and having an office worker spouse correlate with greater willingness to receive the influenza vaccine during pregnancy. Enhanced knowledge and accurate perceptions of influenza and its vaccine influenced willingness. Accumulating knowledge about influenza and its vaccine fosters accurate perceptions. Notably, overall willingness to vaccinate during pregnancy remains low, likely due to safety concerns, and lack of accurate perceptions. Targeted health education, improved communication between healthcare providers and pregnant women, and campaigns highlighting vaccine benefits for mothers and children are essential.